2011
DOI: 10.3109/00498254.2011.614020
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in glutathione S-transferases: Susceptibility and treatment outcome for head and neck cancer

Abstract: The study investigates the association of polymorphism in glutathione S-transferases (GSTs) with susceptibility for head and neck squamous cell carcinoma (HNSCC) and its sites as well as treatment response in cases receiving chemotherapy (CT) and combination of CT-radiotherapy (CT-RT). The case-control study included 500 male cases and an equal number of healthy male controls. Odds ratios (ORs) and 95% confidence intervals (95% CI) were calculated for the association between genotypes and cancer risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…After reading titles, abstracts, 55 articles were retained. For the analysis of GSTM1 or GSTT1 , after discarding 11 articles [7], [12][21] due to the overlapping data and 1 article [22] due to lack of essential genotype information, 44 case-control studies [5], [6], [8][10], [23]–[60] finally met our criteria for inclusion. Among them, 42 studies described the association between GSTM1 null genotype and HNSCC, and 32 between GSTT1 null genotype and HNSCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading titles, abstracts, 55 articles were retained. For the analysis of GSTM1 or GSTT1 , after discarding 11 articles [7], [12][21] due to the overlapping data and 1 article [22] due to lack of essential genotype information, 44 case-control studies [5], [6], [8][10], [23]–[60] finally met our criteria for inclusion. Among them, 42 studies described the association between GSTM1 null genotype and HNSCC, and 32 between GSTT1 null genotype and HNSCC.…”
Section: Resultsmentioning
confidence: 99%
“…However, more than twenty independent studies from various populations have further examined the relationships between these two genes and HNSCC risk, and still reported conflicting results. Some studies in HNSCC have indicated that the null genotype of GSTM1 or GSTT1 is a risk factor of HNSCC development [5][7]. However, such an association was not observed in some other groups [8][10].…”
Section: Introductionmentioning
confidence: 97%
“…Many previous studies have reported that glutathione S-transferases may play an important role in determining the efficacy of chemotherapy on cancer (Ruwali et al, 2011;Suneetha et al, 2011;Bai et al, 2012;Goričar et al, 2015); however, the results of subsequent studies have shown the inconsistent nature of this relationship.…”
Section: Discussionmentioning
confidence: 57%
“…Although comparative analysis did not reveal statistical differences between patient group and controls, GSTM1 null genotypes were more frequents in hyposmic patients with nasal polyposis than in controls. Scientific studies showed that GSTP1 gene polymorphism could influence on the one hand the metabolic activation and also the detoxification of xenobiotics and is therefore, a link between the gene variants and individual susceptibility to different inflammatory disorders (21,22) but only few studies investigated the relationship between Ile105Val GSTP1 polymorphism, nasal polyposis and hyposmia. The results of our study show no correlation between this genetic variant, nasal polyposis and hyposmia, in agreement with one of the few published researches on this subject (23).…”
Section: Discussionmentioning
confidence: 99%